Strategies for Managing the Habitat of the Tapanuli Orangutan (Pongo tapanuliensis) in Bulu Mario and Aek Batang Paya Villages, South Tapanuli - Triani, Hesty; Zahrah, Ma’rifatin; Aththorick, Alief (Manunggal Halim Jaya, 2025)
The Tapanuli orangutan (Pongo tapanuliensis) is a large ape endemic to Sumatra that is critically endangered, with a population of less than 800 individuals. The main pressures on the survival of this species are habitat degradation and increasing negative interactions with local communities around the Batang Toru Ecosystem. This study aims to analyse orangutan habitat management strategies in Bulu Mario and Aek Batang Paya villages, Sipirok sub-district, South Tapanuli regency, which are located in Other Use Areas (APL) and Production Forests. Research tools included cameras, GPS, ArcGIS 10.8, and Expert Choice for AHP data processing. Research materials included 50 cm resolution Pleiades Neo imagery (2023), Indonesian topographic maps, administrative maps, forest area function maps, literature, and questionnaires. Results showed that land cover was dominated by primary forest (43.2%) and secondary forest (40.5%). Thirty-six types of forage vegetation were identified at the tree level (80 individuals/ha) and 33 types at the pole level (239 individuals/ha), while nest trees consisted of 35 types at the tree level (70 individuals/ha) and 30 types at the pole level (243 individuals/ha). The socio-economic conditions of the community are still low, with the majority being farmers, so conflicts often arise due to orangutans eating crops, especially durians. SWOT-AHP analysis resulted in a management strategy that emphasises the development of community agricultural products, reduction of illegal logging, strengthening of multi-stakeholder collaboration, and development of conservation-based ecotourism. The main priority is set on the economic aspect, particularly increasing agricultural yields, as this factor is most decisive for the success of conservation. The implications of this study indicate that Tapanuli orangutan conservation efforts must be integrated with improving the welfare of local communities. Further research is needed to identify leading agricultural commodities and sustainable agroforestry systems, as well as to develop mechanisms for resolving human–animal conflicts, for example, through compensation systems, community-based ecotourism, or payments for environmental services.